2008
DOI: 10.4315/0362-028x-71.11.2339
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks Where Food Workers Have Been Implicated in the Spread of Foodborne Disease. Part 4. Infective Doses and Pathogen Carriage

Abstract: In this article, the fourth in a series reviewing the role of food workers in foodborne outbreaks, background information on the presence of enteric pathogens in the community, the numbers of organisms required to initiate an infection, and the length of carriage are presented. Although workers have been implicated in outbreaks, they were not always aware of their infections, either because they were in the prodromic phase before symptoms began or because they were asymptomatic carriers. Pathogens of fecal, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 162 publications
0
95
0
5
Order By: Relevance
“…In previous studies, the risks of household transmission of Salmonella ranged from 6% to 39% (33,34). The prolonged shedding of NTS postinfection is an important issue, as evidenced by sporadic outbreaks traced back to asymptomatic carriers as the source of infection (35)(36)(37). These findings have important implications for the detection of possible transmission events suspected by public health genomic surveillance of S. Typhimurium infections.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the risks of household transmission of Salmonella ranged from 6% to 39% (33,34). The prolonged shedding of NTS postinfection is an important issue, as evidenced by sporadic outbreaks traced back to asymptomatic carriers as the source of infection (35)(36)(37). These findings have important implications for the detection of possible transmission events suspected by public health genomic surveillance of S. Typhimurium infections.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011 in the United States, an outbreak involving Escherichia coli O157:H7 in which one person died and twelve people became ill was attributed to improper handwashing (Herzog, 2011). Todd et al (2008), analyzed 816 foodborne outbreaks and found that improper handwashing played a large role in the outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Hands are known to be an important vehicle for the transmission of NoV (Bidawid et al 2004;Todd et al 2008;Moe et al 2001), and the use of hand hygiene products that are effective at removing or inactivating NoV is likely to be a critical part of an effective NoV infection control strategy (Bidawid et al 2004;Lages et al 2008;Kampf et al 2005). Despite the important role of hands in the transmission of NoV, little is known about the efficacy of hand hygiene practices in reducing the spread of NoV.…”
Section: Introductionmentioning
confidence: 99%